Synthesis and Characterization of Some New Thermal Stable Polymers - Polymerization of N-[4-N´ -(Benzylamino-carbonyl)phenyl]maleimide - B. L. Hiran; Jyoti Chadhary; S. N. Paliwal; Suresh Meena; P. R. Chaudhary (E-Journal of Chemistry)
This article describes the synthesis and characterization of homopolymer (H-BCPM) of N-[4-N'-(benzylamino-carbonyl) phenyl] maleimide (N-BACPMI) and copolymer (C-BCPM) of N-BACPMI with n-butyl acrylate (BA). The new monomer was synthesized from p-aminobenzoic acid, maleic anhydride and benzylamine. The homopolymerization of N-BACPMI is initiated by free radical using AIBN in THF solvent at 65°C. Radical copolymerization of N-BACPMI with BA, initiated by AIBN, was performed in THF solvent using equimolar amount. Effect of the different free radical initiator AIBN, BPO and solvents p-Dioxane, THF, DMF and DMSO was studied. Homopolymer and Copolymer were characterized by intrinsic viscosity, solubility test, FT-IR, 1H-NMR spectral analysis and elemental analysis. Thermal behaviour was studied by Thermo gravimetric analysis.